Endogenous labour supply and negative economic shocks in a large scale spatial CGE model of the European Union - Martin Aarøe Christensen; Damiaan Persyn (European Commission, Joint Research Centre (JRC), 2022)
We introduce endogenous labour supply decisions with an extensive and intensive margin in a spatial computational general equilibrium model. We show that endogenising labour supply generates an additional economic loss from a negative economic shock compared to a model with fixed labour supply. Adjustments at both the intensive margin (average hours worked) and the extensive margin (labour market participation) contribute to the higher cumulative loss in employment, consumption and GDP. We show that country-level results hide substantial heterogeneity at the regional level due to regional variations in labour market characteristics and economic structures. The results carry important lessons for macro-economic models used for policy evaluation: economic effects may be underestimated by models with fixed labour supply or models considering only the intensive margin of labour supply. Aggregate country level estimates may hide large differences in effects observed at the regional level.
Keywords: 330; Arbeitsangebot; Schock; Arbeitsnachfrage; Wirtschaftslage; Räumliche Verteilung; CGE-Modell; Makroökonomisches Modell; EU-Staaten